Epidemiology Of Trichostrongyles Of Sheep Grazing Under Oil Palm - Aruputham, Sam Mohan (1995)

(untitled)
Endoparasitism is one of the major constraints to the sheep industry in Malaysia. In order to formulate control measures for endoparasitism an understanding of the epidemiology of the infrapopulation and suprapopulation is required. Therefore an epidemiological study of trichostrongyles in sheep was conducted. The pattern of faecal egg output in lambs was observed for twelve months. Infection was first observed at six weeks of age, peaked at twelve weeks, then steadily decreased till it stabilised after eight months, thus indicating an acquired immunity trichostrongyles around eight months. Periparturient rise in egg counts was seen in ewes with a sharp increase in epg one month before and for two months after parturition. From the meteorological parameters monitored, it showed that rainfall and temperature influenced the egg output profile.Pooled faecal culture of samples from Iambs and ewes showed that Haemonchus sp. was the predominant species, followed by Trichostrongylus sp., while larval counts of Oesophagostomum sp. and Cooperia sp. did not exceed 5%. In the lambs and ewes that died total worm counts had more numerous Haemonchus contortus than Trichostrongylus colubriformis. Two techniques for larval recovery from herbage were compared. The recovery rate by the Modifted Parfitt1s technique was 25% and by the Modified Baermann's technique was 33%. There was no consistent relationship between larval recovery and weight of fresh herbage collected during wet and dry periods. The time of development of infective larvae (L3) was measured in the field in both wet and dry periods. In both periods L3 emerged from faecal samples on day four and was present on herbage on day six with the highest number of larvae being present on day seven. Monitoring of the survival of L3 found on herbage showed negligible numbers of L3 after week seven in the wet period and negligible numbers of L3 at week five in the dry period.